Etiology of Hematuria in Children: A Review Article : Etiology of Hematuria in Children - Akhavan Sepahi, Mohsen; Akhavan Sepahi, Mohammad Hoseinn (Journal of Pediatric Nephrology, 2023)
Please Click Here and Go to Continuing Medical Education (CME) Background and Aim: The etiology of hematuria in children is different. Hematuria is a known risk factor for developing chronic kidney disease (CKD). This narrative review aimed to evaluate the etiology of hematuria in children, mainly new hematuria research, to provide an update on the management, and complications that can improve the prognosis of hematuria. Methods: For this narrative review, articles from several sources, including Scopus, Google Scholar, Embase, Web of Science, PubMed, and the Directory of Open Access Journals were used. Results: Kidney and urinary tract infection (UTI) is the most common cause of hematuria in children. Renal structural abnormalities, hypercalciuria, urinary stones, and extrarenal abnormalities associated with hematuria. Conclusion: Hematuria is a symptom and very dangerous, but due to various causes in these patients, it is needed in all patients. The challenge for pediatric nephrologists is the early diagnosis of children with progressive forms of kidney disease from other causes. This manuscript reviews the multiple potential causes of microscopic hematuria and provides a framework for the initial assessment and monitoring of such patients. No internationally accepted, uniform, evidence-based algorithm exists for its diagnostic evaluation anywhere. It is recommended that extensive public attention be paid to the etiology and management of hematuria. Please Click Here and Go to Continuing Medical Education (CME)